2008
DOI: 10.1123/ijspp.3.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Cold Water Immersion Following Cycling in the Heat

Abstract: Cold water immersion (CWI) has become a popular means of enhancing recovery from various forms of exercise. However, there is minimal scientific information on the physiological effects of CWI following cycling in the heat.Purpose:To examine the safety and acute thermoregulatory, cardiovascular, metabolic, endocrine, and inflammatory responses to CWI following cycling in the heat.Methods:Eleven male endurance trained cyclists completed two simulated ~40-min time trials at 34.3 ± 1.1°C. All subjects completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
56
1
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 19 publications
(26 reference statements)
11
56
1
8
Order By: Relevance
“…The significant faster cooling rate following CWI was observed in the first 6 minutes (Lee et al, 2012) and last for mostly 40 minutes (Halson et al, 2008). Gradual decreases in core temperature and significant difference between post-CWI 35 and 40 minutes were found comparing with passive recovery (Peiffer et al, 2009).…”
Section: Endurance Performance Recoverymentioning
confidence: 69%
See 3 more Smart Citations
“…The significant faster cooling rate following CWI was observed in the first 6 minutes (Lee et al, 2012) and last for mostly 40 minutes (Halson et al, 2008). Gradual decreases in core temperature and significant difference between post-CWI 35 and 40 minutes were found comparing with passive recovery (Peiffer et al, 2009).…”
Section: Endurance Performance Recoverymentioning
confidence: 69%
“…CWI recovery intervention is believed to have positive effect particularly on endurance performance recovery, which may be related to successful reduction on core temperature (Crowe et al, 2007;Halson et al, 2008;Vaile et al, 2008;Peiffer et al, 2009;Peiffer et al, 2010;Vaile et al, 2011;Lee et al, 2012) with enhanced cooling rate during the immersion (Lee et al, 2012;Pointon et al, 2012). The significant faster cooling rate following CWI was observed in the first 6 minutes (Lee et al, 2012) and last for mostly 40 minutes (Halson et al, 2008).…”
Section: Endurance Performance Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…To date, numerous passive and active recovery methods have been trialed, such as carbohydrate replenishment, stretching and massage, with water immersion representing a popular application (Cochrane, 2004;Halson et al, 2008). Of relevance, a recent study by Ingram et al (2009) reported that cold water immersion (CWI), as opposed to contrast (hot and cold) water therapy and a control condition, resulted in a more rapid return to baseline exercise (running) performance in male athletes.…”
Section: Introductionmentioning
confidence: 99%